Aggressive Behavior of Students at PGRI 2 Padang High School (Student Case Study) - Putri Dellis, Elsa; Fuaddillah Putra; Rahmawati Wae (Global Action and Education for Society, 2025)
This research is motivated by the presence of students involved in physical aggressive actions (hitting, kicking), verbal aggressive (insults, shouting), explosive anger, and hostility towards peers and school authorities. The purpose of this study is to describe the aggressive behavior of students at SMA PGRI 2 Padang, which is seen from the characteristics of physical aggression, verbal aggression, anger, and hostility. This study uses a descriptive qualitative approach. The key informants of this study are MFA as key informants and additional informants namely FD, RK, MR. Data collection techniques used in this study are observation and interviews. Data analysis techniques have 3 stages: data reduction, data presentation and drawing conclusions and verification. The results of the study revealed that aggressive behavior of students at SMA PGRI 2 Padang, manifested in four main characteristics: 1) physical aggression, shown through actions such as pushing, hitting, or kicking, often triggered by teasing or provocation from friends, and occurring in school areas with minimal supervision. 2) verbal aggression, including the use of harsh words, teasing, sarcasm, and shouting as a response to feeling offended or humiliated, often occurring in class or during gatherings. 3) anger in the form of spontaneous emotional outbursts such as shouting, nagging, or other impulsive actions, arises when feeling underestimated or treated unfairly, and is vented to reduce emotional stress. 4) hostility, shown through attitudes of distancing, ignoring, insinuating, or influencing other friends to join in the hostility, as a reaction to painful experiences or unresolved conflicts. Based on the results of this study, it is recommended that guidance and counseling teachers provide ongoing counseling services, both individual and group, that focus on emotional regulation, social skills and empathetic communication.